PENGEMBANGAN TEKNOLOGI SELEKSI IN VITRO BERULANG (REPEAT CYCLING–IN VITRO SELECTION) TOLERAN STRES KEKERINGAN UNTUK PERBAIKAN MUTU GENETIK DAN PRODUKSI TANAMAN KEDELAI BERMIKORIZA - Riduan, Ahmad; Rainiyati, Rainiyati; Alia, Yulia (LPPM Universitas Jambi, 2017)
Every plant rhizospheres in any ecosystem there are various living microorganisms including Arbuscular Mycorrhizae Fungi (AMF). An isolation and characterization is required to investigate the species or type of the AMF. This research was aimed at studying the isolation and characterization of AMF sporulation in soybean rhizospheres in Jambi Province. The results of evaluation on soil samples before trapping showed that there are spores from three genus of AMF twelve types Glomus , two types Acaulospora and one type of Enthrophospora. Following single spore culture in soybean rhizosphere, 5 spore types were obtained: Glomus sp-1, Glomus sp-4, Glomus sp-7, Glomus sp-8 Glomus sp-10.